Early clinical and procedural outcomes in large series of 34‐mm self‐expanding transcatheter aortic valve replacement. Issue 4 (4th December 2019) - Ali, Zuber; Sharma, Payal; Mengesha, Tadele; Dalmar, Ahmed; Ammar, Khawaja Afzal; Allaqaband, Suhail Q.; O'Hair, Daniel P.; Khandheria, Bijoy K.; Jain, Renuka; Bajwa, Tanvir
Abstract: Objectives: We aimed to evaluate early clinical and procedural outcomes with the 34‐mm Evolut R transcatheter aortic valve replacement (TAVR) prosthesis. Background: The 34‐mm Evolut R (Medtronic, Minneapolis, MN) self‐expanding TAVR prosthesis was designed to treat patients with larger annuli. Methods: Clinical, demographic, procedural, and echocardiographic data on consecutive patients who underwent TAVR with a 34‐mm Evolut R prosthesis at our institution were collected and analyzed. Results: One hundred ninety‐six patients underwent TAVR with this prosthesis from November 2016 to July 2018, a majority ( n = 188, 96%) through transfemoral access and with conscious sedation ( n = 182, 93%). Mean age, Society of Thoracic Surgery risk score, and follow‐up were 82 ± 8 years, 5.4 ± 5%, and 8.2 ± 5.3 months, respectively. Mean aortic valve (AV) peak velocity was 4.0 ± 0.6 m/s, mean AV gradient was 38 ± 13 mmHg, AV area was 0.79 ± 0.23 cm 2 ; calcium score was 3, 503 ± 1, 970 Agatston units, and perimeter was 85 ± 4.3 mm. Device implantation was successful in all but one patient. Postprocedure mean AV peak velocity, AV mean gradient, and AV area were 1.9 ± 0.4 m/s, 7 ± 3 mmHg, and 2.6 ± 0.7 cm 2, respectively. New pacemaker requirement rate was 16%, and moderate paravalvular leak was present in six patients (3%), which improved to mild in three patients at 6‐month follow‐up. In‐hospital, 30‐day, 6‐month, and 12‐month survival rates were 98%, 96% (hospital discharge), 96% (30‐day), 89% (6‐month), and 83% (12‐month). Conclusion: These data demonstrate high success and good procedural, echocardiographic, and clinical outcomes of 34‐mm Evolut R in patients with large annuli.